2002
DOI: 10.1159/000063101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surgeons’ Specialty on the Selection of Vascular Access for Hemodialysis Treatment

Abstract: Background/Aim: Various patient-related factors could not explain the variability of access types across facilities in the published literature. The aim of this study was to investigate the influence of surgeons’ specialty on access type selection for hemodialysis treatment. Methods: The directors (nephrologists) of all renal units in Greece (n = 92) were surveyed by a closed questionnaire. Results: The response rate was 75%. There was no statistically significant difference in the percentage of patients predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The influence of creator's specialty on access type selection was found not significant in a previous study (2), and although that impact on access outcomes has not been addressed in comparative studies, there are authors reporting excellent outcomes of AV fistulas created by nephrologists (3, 4). In contrast, creator's level of training was found in DOPPS affecting significantly the type of access placed; for every doubling of the number of fistulas placed during training, there was a 2.2 higher odds of placing a fistula instead of a graft in practice (1).…”
Section: The View Of “Experts”mentioning
confidence: 84%
See 1 more Smart Citation
“…The influence of creator's specialty on access type selection was found not significant in a previous study (2), and although that impact on access outcomes has not been addressed in comparative studies, there are authors reporting excellent outcomes of AV fistulas created by nephrologists (3, 4). In contrast, creator's level of training was found in DOPPS affecting significantly the type of access placed; for every doubling of the number of fistulas placed during training, there was a 2.2 higher odds of placing a fistula instead of a graft in practice (1).…”
Section: The View Of “Experts”mentioning
confidence: 84%
“…II). A meta-analysis was performed using the random effects model because apparent heterogeneity existed between studies (I 2 = 55%). Patency rates were extracted from Kaplan-Meier graphs in the corresponding articles, and the outcome events represented the number of failures in 1 year.…”
Section: The Effect Of Juniors’ Training On Outcomementioning
confidence: 99%
“…Surgeon specialty, as well as surgical center volume, is associated with increased AVF placement over AVG (4,11). To control for surgeon specialty and surgical center volume, all patients in the present study were seen by one of two surgeons, both of whom were dedicated vascular access surgeons averaging greater than 30 access procedures per year.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest contribution of the current report is likely not the algorithm itself, but rather our challenge to think about dialysis access as a complex vascular surgical procedure. Notably Lazarides et al (20) reported from a national survey in Greece that the incidence of native AVFs created by nonvascular surgeons was comparable to that of vascular surgeons. However, the vascular surgeons were more likely to deal with complex access problems and manage the access‐associated complications.…”
Section: Discussionmentioning
confidence: 98%